High throughput isolation of nucleated cells from bone marrow samples using deterministic lateral displacement (DLD) microfluidics technology - Tan, Nicholas Kwan Zen (Nanyang Technological University, 2022)
The growing interest in regenerative medicine has opened new avenues for novel cell therapies using stem cells-rich bone marrow samples. Bone Marrow Aspirate (BMA) is an important source of biological sample as it comprises of the highest source of multipotent progenitor cells for autologous stem cell therapies. However, these cells are extremely rare (0.001% of total nucleated cells). Conventional harvesting methods using centrifugation often led to poor yield and cell viability, thus advocating a need for novel BMA sample preparation technologies. Microfluidics is an emerging technology that has garnered recent involvement in biomedical technology such as cell separation. The focus of this thesis exploits the Deterministic Lateral Displacement (DLD) technique, a passive size-based cell sorting method in microfluidics, to isolate progenitor cells from BMA with improved yield and efficiency. Two DLD devices were proposed and characterized using polystyrene microspheres and whole blood samples. These devices have different pillar shapes and size criteria (critical diameter) with applications to sort nucleated and stromal cells from BMA. The final DLD device was used to process BMA and compared with conventional centrifugation. Our results showed that DLD can achieve a faster processing time with higher cell recovery by at least a factor of 2 as compared to centrifugation. To improve throughput scalability, we also developed a novel multiplexed DLD device and a benchtop portable microfluidic pressure system for sample processing in clinical settings. Taken together, DLD platforms are highly useful for fast and efficient isolation of progenitor cells from BMA for effective downstream cell therapy.